Microstructure and crystallographic orientation dependence of electrical properties in lead zirconate thin films prepared by sol-gel process - Alkoy, EM; Alkoy, S; Shiosaki, T (Japan Soc Applied Physics, 2005)
Lead zirconate (PbZrO(3)) thin films are grown on Pt(111)/Ti/SiO(2)/Si(100) substrates by sol-gel using precursor solutions with stoichiometric and 20 mol % excess Pb. Films with no preferred orientation and [111] pseudocubic texture (denoted as [111](pc)) are obtained by changing the drying temperature at the pyrolysis stage. Randomly oriented films were found to have a two-phase microstructure consisting of large rosette-type perovskite regions with a nanocrystalline phase located in between. The ratio of the rosettes increase to cover the entire surface of the films with the increase of Pb content. The films with [111](pc) orientation have a uniform microstructure with micron size grains. The electrical properties of the films were influenced markedly by the microstructure and orientation of the films. The [111](pc) oriented films exhibit a square-like double hysteresis loop with maximum polarization (P(max)) reaching 61 x 10(-6) C/cm(2) under 550 kV/cm, whereas stoichiometric films with no preferred orientation have a P(max) of 36 x 10(-6) C/cm(2) with slimmer hysteresis curves.
Keywords: lead zirconate; antiferroelectrics; thin films; sol-gel; orientation